Hubungan Rasa Malu dan Kecemasan Sosial pada Mahasiswa Baru Fakultas Psikologi UKSW - Yunanto Hendra Wahyudi; Emmanuel Satyo Yuwono (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
This study aimed to determine the relationship between shyness and social anxiety in new students in the Faculty of Psychology at Satya Wacana Christian University (UKSW). The method used was quantitative, using a simple random sampling technique involving 99 subjects. This study measured shyness and social anxiety using two instruments: the RCBS 13 for shyness and the SAS-A for social anxiety. The collected data were then analyzed using the Pearson Product Moment statistical method to determine the relationship between the two variables. The results showed no significant relationship between shyness and social anxiety in new students, with a correlation (R) of 0.86 and a significance level of 0.398 (P > 0.05). This indicates that high levels of shyness in new students do not directly correlate with their levels of social anxiety. This means that higher levels of shyness do not necessarily lead to increased levels of social anxiety. This finding contradicts several previous studies that suggested a positive relationship between shyness and social anxiety. This study provides new insights into the psychological dynamics experienced by new students, particularly in the UKSW Faculty of Psychology, which should be considered in developing orientation programs or mental health support for new students. Furthermore, these findings also open up opportunities for further research that could explore other factors influencing the relationship between shyness and social anxiety.